Composition of Fatty Acids and Squalene Content of Wild Spinach (Amaranthus dubius Mart) Seed Oil - Soetjipto, Hartati; Krisdayanti, Mitra; Aminu, November Rianto (Makara Journal of Science, 2021)
This study aims to determine the yield of wild spinach seed oil obtained by continuous extraction methods using Soxhlet apparatus for 10.5 hours in n-hexane solvent, the physio-chemical properties, and the composition of wild spinach seed oil using the Gas Chromatography-Mass Spectrometry (GC-MS) method. Refinement of wild spinach seed oil was done by degumming and neutralization. The yield of wild spinach seed oil extraction before refinement was 4.36 ± 0.29% (w/w) while after refinement was 0.68 ± 0.033% (w/w). Physio-chemical properties of wild spinach seed oil after refinement was as follows: water content 0.37%; peroxide value 9.5 meq/kg; acid value of 0.53 mg KOH/g oil; saponification value 208.9 mg KOH/g oil. The results of GC-MS analysis showed that the wild spinach seeds were composed of 5 main components: dodecanoic acid (0.28%); tetradecanoic acid (0.08%); palmitic acid (1.31%); squalene (94.9%); and linoleic acid (3.34%).